BONE TARGETING AGENTS IN PREVENTION OF SKELETAL-RELATED EVENTS IN METASTATIC CANCERS OF SOLID TUMOURS: AN ECONOMIC EVALUATION (Proceedings of the International Conference on Public Health, 2019)
Skeletal related events (SREs) are skeletal complications from bone metastases such as spinal cord compression, pathological fracture, palliative radiation to the bone and bone surgery. These events resulted in greatest morbidity which affecting patients’ quality of life over the years and may increase healthcare cost in treating SREs. Therefore, preventing SREs may reduce the economic burden to health care. Bone targeting agents (BTA) significantly delayed time-to-first SREs and reduced the risk of first and subsequent SREs in majority of cancers. Among all BTA, denosumab and zoledronic acid are the most effective and commonly used in preventing SREs. The objective of this evaluation was to assess the cost-effectiveness  of  BTA in  prevention  of  SREs in  metastatic cancer  of  solid  tumours and its financial implication. The economic evaluation was designed from provider perspective (Ministry of Health, Malaysia) using literature-based Markov model to compare the costs and quality adjusted life years (QALY) for hypothetical cohort of patients with primary solid tumour with bone metastases. Based on the model, the use of BTA in preventing skeletal-related events among solid tumour patients with bone metastases is a cost-effective strategy.  Within this evaluation, the most cost-effective option was 12-weekly intravenous Zoledronic acid, yielding an incremental cost-effectiveness ratio of RM 4,969 per QALY gained. The estimated total financial implication for this strategy was RM 8.8 million per year. In conclusion, 12-weekly Zoledronic acid is the most cost-effective option in preventing SREs in solid tumour cancer patients with bone metastasis.
Keywords: skeletal-related events, bone metastases, cost-effectiveness analysis, economic evaluations